PENGARUH LATIHAN PLYOMETRIC SQUAT JUMP TERHADAP KEMAMPUAN SHOOTING - Yoan Hermawan (Journal of Physical Education and Sport Science, 2022)
The Influence of Plyometric Squat Jump on Soccer Shooting Ability in PS PLUTO Luragung Tonggoh". The purpose of this study was to determine: The Effect of Plyometric Squat Jump on Soccer Shooting Ability in PS PLUTO Luragung Tonggoh. This study uses experimental research methods. The population and sample in this study PS PLUTO players, totaling 15 players. With the sampling technique using total sampling, in order to obtain a sample of 15 players. The research instrument used in this study was a shooting test. The results of the analysis and processing of pre-test data obtained the lowest score of 5, the highest score of 11, and an average of 7.9. Meanwhile, the post-test data obtained the lowest score of 7, the highest score of 15, and an average score of 10.6. This shows an increase in the ability to shoot football. Based on the test, it shows that the two tests have a normal distribution. Therefore, to test the hypothesis using the Independent Samples Test, the pre-test and post-test values ​​showed a sig. (2-tailed) value of 0.002 <0.05, so there was a significant difference. So H0 is rejected and Ha is accepted. This means that there is a plyometric squat jump effect on soccer shooting ability at PS PLUTO Luragung Tonggoh.